A new subgradient extragradient method for solving the split modified system of variational inequality problems and fixed point problem - Anchalee Sripattanet; Atid Kangtunyakarn (My University, 2022)
Abstract We introduce a new subgradient extragradient algorithm utilizing the concept of the set of solutions of the split modified system of variational inequality problems (SMSVIP). Our main theorem is weak convergence theorem for such an algorithm for approximating the fixed point problem in a real Hilbert space. We also apply these results to approximate the split minimization problem. In the last section, we provide an example to illustrate the potential of our main theorem.
Keywords: Subgradient method; Optimization and Variational Analysis